German Soldiers' Needs to Clarify Open Aspects in Their Life, to Talk About Fears and Worries, and to Forgive and to Be Forgiven as a Matter of Life Reflection - Büssing, Arndt; Recchia, Daniela Rodrigues; Toussaint, Loren L. (Frontiers in Psychiatry, 2018)
Background: In missions, soldiers are confronted with difficult situations which may impair their physical and mental health. As the resulting problems are commonly regarded as stigmata, soldiers may obviate talking about their experiences and try to oppress them. It was aim of this study to clarify whether soldiers do perceive needs to reflect back on life, to seek release from ‘open aspects’ of their life, and to talk with others about fears and worries, to forgive others or to be forgiven. Further we intended to clarify whether these needs were related to stress perception, PTSD symptoms and reduced life satisfaction on the one hand, and religious trust as a resource to cope on the other hand. Methods: Cross-sectional survey of 1,097 German soldiers (92% men). Existential/spiritual needs and mental health indicators, including stress perception, PTSD symptoms, life satisfaction, were assessed using standardized questionnaires. Results: For 30% of soldiers it was important to reflect on life, 23% had a strong need to clarify open aspects of life, 30% had a strong need to talk with others about their about fears and worries, 13% had strong needs to forgive, and 13% had a strong need to be forgiven. Soldiers´ needs to clarify open (and probably conflicting) aspects of life were moderately related to their intention to forgive others and to be forgiven (rs > .35). Soldiers treated in the hospital for psycho-mental trauma had significantly higher needs scores than soldiers still serving on active duty, particularly for the need to talk with others (F = 39.1; p < .0001) and to be forgiven (F = 26.0; p<.0001). Across all soldiers the best predictors of these needs were PTSD symptoms and stress perception, albeit with relatively weak predictive power (beta < .25; R2s <.24). Conclusions: The process of life reflection and subsequent intention to solve conflicting situations and experiences can be considered a process of coping with one’s own failures, guilt, and mistakes. It should be noted that these needs were significantly stronger in soldiers with trauma. Addressing unmet needs may help them to communicate and to reject the stigma of ‘weakness’.